Pan-immune-inflammation Value and Prognosis in Patients With Esophageal Cancer - Yoshifumi Baba, MD, PhD, FACS; Shigeki Nakagawa, MD, PhD; Tasuku Toihata, MD, PhD; Kazuto Harada, MD, PhD; Masaaki Iwatsuki, MD, PhD, FACS; Hiromitsu Hayashi, MD, PhD, FACS; Yuji Miyamoto, MD, PhD, FACS; Naoya Yoshida, MD, PhD, FACS; Hideo Baba, MD, PhD, FACS (Annals of Surgery Open, 2022)
Mini-abstract:. The pan-immune-inflammation value was associated with clinical outcomes and tumor-infiltrating lymphocytes in 866 esophageal cancers. Systemic immune competence may influence patient prognosis through local immune response. Objective:. To examine the relationship between the pan-immune-inflammation value (PIV), tumor immunity, and clinical outcomes in 866 patients with esophageal cancer. Background:. The PIV, calculated from all immune-inflammatory cells in the peripheral blood count, is a recently proposed marker for clinical outcomes in some types of cancers. Nonetheless, the prognostic significance of PIV in esophageal cancer remains unclear. Methods:. In the derivation cohort (n = 433), we set the optimal cutoff value using a time-dependent receiver operating characteristic (ROC) curve. In the validation cohort (n = 433), the relationships between the PIV, tumor-infiltrating lymphocytes (TILs), CD8 expression by immunohistochemical staining, and patient prognosis were examined. Results:. The area under the ROC curve for the PIV at 5 years was 0.631 in the derivation cohort. The validation cohort, divided into PIV-low cases (n = 223) and PIV-high cases (n = 210), showed significantly worse overall survival (log-rank P = 0.0065; hazard ratio [HR]: 1.48; 95% confidence interval [CI]: 1.12–1.98; P < 0.001; multivariate HR: 1.41; 95% CI: 1.05–1.90; P = 0.023). The prognostic effect of the PIV was not significantly modified by any clinical characteristics (P for interaction > 0.05). The PIV-high cases were significantly associated with a low TIL status (P < 0.001) and low CD8-positive cell counts (P = 0.011). Conclusions:. The PIV was associated with clinical outcomes in esophageal cancer, supporting its role as a prognostic biomarker. Considering the relationship between the PIV and TILs, systemic immune competence may influence patient prognosis through a local immune response.